Factors affecting packed and unpacked fluid milk consumption in Wolaita Zone, Ethiopia - Kuma, B.; Baker, Derek; Getnet, Kindie; Kassa, B. (2012)
This study was conducted to identify factors affecting packed and unpacked fluid milk consumption preferences of households in Wolaita zone. A total of 194 randomly sampled consumer households of 3 towns of Waliata zone were studied using semi-structured questionnaire. All the data collected were analyzed using Multinomial Logit Model. The result obtained indicated that 78.4% of the households consumed only unpacked fluid milk, 7.7% of households consumed only packed fluid milk and 13.9% of households consumed both unpacked and packed fluid milk. Multinomial Logit model results showed that variables such as age of household heads, income level of households, households with at least a child under six years of age and milking cow, households who disagree with the statement 'packed fluid milk fattens children' and households who disagree with the statement 'advertisement influences people to buy more packed fluid milk', significantly affected consumption of unpacked fluid milk. Education status of household heads, young aged household heads, medical prescription, households who accept the statement 'sterilized milk contains preservatives' reported to have consumed packed fluid milk. Moreover, consumers who agree with the statement 'price of packed fluid milk is expensive compared with unpacked fluid milk' were less likely to consume packed fluid milk. The general implication is that a significant portion of unpacked fluid milk is reported to be consumed in the study area without quality and hygienic inspection. This situation seems to warrant the governments to introduce new policy tools to improve the hygiene and quality of unpacked fluid milk. Milk producing and processing companies need to design better pricing, promotion and advertising strategies for fluid milk consumption to attract consumers. Furthermore, fluid milk processing enterprises and importers need to improve their processing technological status aimed at reducing cost of processing and marketing to attract consumers.